Neuropsychiatric disorders in Wilson’s disease: literature review - S. Galnaitytė; A. Musneckis (Neurologijos seminarai)
Wilson’s disease is a rare autosomal recessive disease due to the pathogenic mutations in the ATP7B gene that causes impaired copper excretion in the liver and its accumulation in tissues and organs. Clinically, the disorder of copper metabolism is manifested by various symptoms, usually changes in the liver function, neuropsychiatric symptoms, and Kayser-Fleischer rings in the cornea. Wilson’s disease can be manifested by various neuropsychiatric disorders: cognitive and executive function, sleep and mood disorders, personality changes, or psychosis. Diagnosis of the disease is often delayed, especially when psychiatric symptoms appear. The mechanism of these symptoms is not clear, and the data of the conducted studies are controversial. Copper chelators and zinc are prescribed for the treatment. In order to treat mental disorders, psychotropic drugs and psychotherapy can be used. It is important for healthcare professionals to understand the link of the symptoms of Wilson’s disease and neuropsychiatric disorders in order to achieve timely disease diagnosis and effective treatment. In this article, we review the latest literature on neuropsychiatric disorders in people with Wilson’s disease, their causes, diagnosis, and treatment recommendations.